Nitrogen excretion during embryonic development of the green iguana, Iguana iguana (Reptilia; Squamata) - Sartori, M. R. (2012)
Development within the cleidoic egg of birds and reptiles presents the embryo with the problem of accumulation of wastes from nitrogen metabolism. Ammonia derived from protein catabolism is converted into the less toxic product urea or relatively insoluble uric acid. The pattern of nitrogen excretion of the green iguana, Iguana iguana, was determined during embryonic development using samples from allantoic fluid and from the whole homogenized egg, and in hatchlings and adults using samples of blood plasma. Urea was the major excretory product over the course of embryonic development. It was found in higher concentrations in the allantoic sac, suggesting that there is a mechanism present on the allantoic membrane enabling the concentration of urea. The newly hatched iguana still produced urea while adults produced uric acid. The time course of this shift in the type of nitrogen waste was not determined but the change is likely to be related to the water relations associated with the terrestrial habit of the adult. The green iguana produces parchment-shelled eggs that double in mass during incubation due to water absorption; the eggs also accumulate 0.02. mM of urea, representing 82% of the total measured nitrogenous residues that accumulate inside the allantois. The increase in egg mass and urea concentration became significant after 55. days of incubation then were unchanged until hatching. © 2012 Elsevier Inc.